2009
DOI: 10.1080/00071660802629571
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and quality properties of meat from broiler chickens reared under different monochromatic light sources

Abstract: 1. Quality properties of breast and drumstick muscles of female broiler chickens reared under different light sources were evaluated using a total of 480 female chicks (Ross 308). 2. After hatch, the chicks were randomly divided into three lighting treatment groups: control (daylight; mini incandescent lamps), G-B lighting group (green light monochromatic (MC) lamps for first 3 weeks switching to blue MC lamps for remaining 3 weeks), G-GB mixed lighting group (Green MC light for first 3 weeks, switching to Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 16 publications
6
42
0
3
Order By: Relevance
“…Light, for instance, is a critical environmental factor for manipulating the feed intake. By artificially increasing the length of time the bird is subjected to light, its feed intake can be increased; a technique employed in modern poultry systems to favour high growth rates (Olanrewaju et al 2006;Karakaya et al 2009). It is possible that improved housing conditions (ambient temperature and humidity, air flow etc.)…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
“…Light, for instance, is a critical environmental factor for manipulating the feed intake. By artificially increasing the length of time the bird is subjected to light, its feed intake can be increased; a technique employed in modern poultry systems to favour high growth rates (Olanrewaju et al 2006;Karakaya et al 2009). It is possible that improved housing conditions (ambient temperature and humidity, air flow etc.)…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
“…Varity of previous conducted studies demonstrate the effects of light criteria on bird health and immunity with special references to light color and spectrum, Rozenboim et al (1999) found that maximization of monochromatic light effect on growth and welfare in broiler chickens is achieved by age of birds, also, Karakaya et al (2009) found that rearing broiler under green light at an early age and blue light in older one could improve growth performance and meat quality properties, while, Rozenboim et al (2004) stated that switching light from blue to green at 20 day age could improve growth performance of male broiler chickens. Moreover, Xie et al (2008) found that immune response of broilers was enhanced under green and blue light.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that green light may be required for broiler growth. In study of Karakaya et al(2009), only female broilers were used and performance in response to light is expected to be different between males and females, as found in the present study. Santana et al (2014) did not find any broiler performance differences when LED or fluorescent light were used.…”
Section: Discussionmentioning
confidence: 59%
“…Other researchers also obtained better broiler performance with colored lights. Karakaya et al (2009), for instance, found significantly higher feed intake, body weight and total muscle weight in broilers reared under green light or combined blue and green light compared with those reared under white incandescent light. This suggests that green light may be required for broiler growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation